The Integral Role of Pharmacists, Laboratory Professionals, and Nurses in Enhancing Medication Management during Physical Therapy Rehabilitation for Patients with Chronic Illnesses - ALQAFLAH, MOTEB AREF; Daghriri, Hamad Ahmed Ali; Alqhatani, Ibrahim Mohammed Mushabbab; ALFEHAID , MOHAMED ABDULAZIZ ALI; Alfehaid , Meshari Ali Meshari; ALFEHAID , ALI ABDULAZIZ ALI; zain, Alhussain mohammed; Shwaikan, Bayan Ahmad; AL dawsari, Nasser jamaan nasser; Somily, Amnah Ahmad Musawi; aamer, Bashier mousi; alshamri , Magbulaha habas; et al. (Journal of Ecohumanism, 2024)
Background: Chronic diseases are a primary source of morbidity and death worldwide, needing appropriate treatment approaches. An interprofessional healthcare team, consisting of pharmacists, laboratory specialists, and nurses, is crucial in optimizing drug regimens and increasing patient outcomes throughout physical therapy rehabilitation programs. This research investigates the joint responsibilities of these experts in chronic illness management. Methods: A systematic review was carried out utilizing databases such as Google Scholar, PubMed, Scopus, EBSCO, and the Cochrane Library. The search looked for papers from 2010 to 2023 that utilized phrases like "pharmacist," "laboratory technician," "interprofessional healthcare," and "chronic disease." Results: The results demonstrate how important pharmacists are to medication management, including patient education, medication reconciliation, and drug interaction monitoring. The coordinated efforts of pharmacists, nurses, and laboratory specialists result in better treatment results and higher patient satisfaction. Effective communication and coordination within the interprofessional team are critical for reducing medication mistakes and adhering to treatment plans. Conclusions: In conclusion, multidisciplinary care teams that include pharmacists, lab specialists, and nurses greatly improve drug schedules during physical therapy rehabilitation. This partnership not only improves clinical results, but it also raises the quality of care delivered to patients with chronic diseases. Future study should concentrate on building frameworks for improving interprofessional cooperation and investigating the long-term effects of these practices on patient health.